Leçon de courage — à la frontière de la littérature et de la philosophie - Marsó, Paula (Verbum – Analecta Neolatina, 2010)
From the beginning of his career in The First Discourse to the end in Reveries of the Solitary Walker, Rousseau makes it clear that the problem of self-knowledge is a central theme in his writings. How is self-knowledge possible? Can it be a valid subject of enquiry for philosophy or literature? How can autobiography be an authentic instrument between philosophy and fiction?